若4a^xb^3与-3a^2b^2x+y的差仍为单项式,求多项式(3x+2y)^2-5(3x-2y)+7(3x+2y)^2-(3x-2y)的值

来源:学生作业帮助网 编辑:作业帮 时间:2024/04/28 08:14:32
若4a^xb^3与-3a^2b^2x+y的差仍为单项式,求多项式(3x+2y)^2-5(3x-2y)+7(3x+2y)^2-(3x-2y)的值

若4a^xb^3与-3a^2b^2x+y的差仍为单项式,求多项式(3x+2y)^2-5(3x-2y)+7(3x+2y)^2-(3x-2y)的值
若4a^xb^3与-3a^2b^2x+y的差仍为单项式,求多项式(3x+2y)^2-5(3x-2y)+7(3x+2y)^2-(3x-2y)的值

若4a^xb^3与-3a^2b^2x+y的差仍为单项式,求多项式(3x+2y)^2-5(3x-2y)+7(3x+2y)^2-(3x-2y)的值
4a^xb^3与-3a^2b^2x+y的差仍为单项式,则4a^xb^3与-3a^2b^2x+y为同类项.
x=2,2x+y=3
解得 x=2,y=-1
(3x+2y)^2-5(3x-2y)+7(3x+2y)^2-(3x-2y)
=8(3x+2y)^2-6(3x-2y)
=8*【3*2+2*(-1)】^2-5*【3*2-2*(-1)】
=8*4^2-5*8
=88